Rekonstruksi Kurikulum Pendidikan Islam (Analisis Pengembangan dan Materi Pendidikan Islam) - Chanifudin Chanifudin; Tuti Nuriyati; Nasrun Harahap (STAIN Bengkalis, 2020)
To achieve a goal in education requires a guide in implementation. The guide is then known as curriculum terms. Curriculum is an educational guide or program that contains teaching materials, experiences that are compiled, programmed, planned, and planned systematically based on the norms used as a guide in the learning process to achieve a goal in education. With the rapid development of Islamic education, it is difficult to imagine how the development of Islamic education without the adequate curriculum or in accordance with the development needs of the times. However, along with the development of the times there are various demands that Islamic education must be able to answer the needs of the times. On the other hand, there is still a lot of Islamic education that uses the old curriculum. As a result, in many cases Islamic education is less able to contribute to the development of the era. Therefore, it is necessary to have a curriculum that is able to answer these changes based on the development and material of Islamic education. This is the urgency of this article.